2011
DOI: 10.4093/dmj.2011.35.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviruses Expressing PDX-1, BETA2/NeuroD and MafA Induces the Transdifferentiation of Porcine Neonatal Pancreas Cell Clusters and Adult Pig Pancreatic Cells into Beta-Cells

Abstract: BackgroundA limitation in the number of insulin-producing pancreatic beta-cells is a special feature of diabetes. The identification of alternative sources for the induction of insulin-producing surrogate beta-cells is a matter of profound importance. PDX-1/VP16, BETA2/NeuroD, and MafA overexpression have been shown to influence the differentiation and proliferation of pancreatic stem cells. However, few studies have been conducted using adult animal pancreatic stem cells.MethodsAdult pig pancreatic cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Previous studies have demonstrated that differentiated insulinproducing cells from non-β-cells are useful sources to overcome the shortage of human islets for transplantation [16,[24][25][26][27]. In this study, we demonstrated that mouse small intestinal cells could be induced to differentiate into insulin-producing To improve the efficiency of transduction, we found a specific arterial delivery system for the induction of genes combined with PMB into the small intestine.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have demonstrated that differentiated insulinproducing cells from non-β-cells are useful sources to overcome the shortage of human islets for transplantation [16,[24][25][26][27]. In this study, we demonstrated that mouse small intestinal cells could be induced to differentiate into insulin-producing To improve the efficiency of transduction, we found a specific arterial delivery system for the induction of genes combined with PMB into the small intestine.…”
Section: Discussionmentioning
confidence: 81%
“…It is important that transcription factors are turned on and off at appropriate times for determining cell fate. PDX1 alone has little activity or it induces other pancreatic cells; however, it becomes a potent factor when it interacts with NEUROD1 [37,38]. Another important transcription factor for β-cell-specific differentiation is MAFA [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been tested both in vitro and in vivo. The adenovirus-mediated overexpression of Pdx1, NeuroD and MafA was shown to induce insulin gene expression in porcine neonatal pancreas non-endocrine cells but not in adult pig pancreatic cells [72]. Pdx1 transduction into human pancreatic ductal cells induced insulin gene expression [73].…”
Section: Pdx1 Neurod and Mafamentioning
confidence: 96%